Emerging effect of anesthesia on post-operative tumor recurrence and metastasis. Issue 8 (August 2019) - Wang, Weilian; Xiao, Jinliang; Shen, Shuwei; Wang, Shu; Chen, Minghao; Hu, Ya
Post-operative recurrence and metastasis of malignant tumors are difficult to control, which probably results from multiple factors that affect the prognosis and the undefined mechanism. Anesthesia may be an influential factor. Researchers have performed many meaningful studies on the relationship between anesthetic drugs/methods and tumor growth/immune function, which provide important references for the anesthetic selection and peri-operative management of tumor patients. Anesthetics, analgesics, and sedatives should be used with caution because their effects in post-operative patients remain controversial. This review summarizes the emerging progress on the effect of anesthesia on post-operative tumor recurrence and metastasis, particularly focusing on the effects of anesthetic drugs, anesthetic methods, and post-operative analgesia on tumor growth and metastasis. Future studies should provide strict criteria for the proper use of anesthetics in patients with malignant tumors and provide experimental evidence for the improvement and development of novel anesthetics and anesthetic methods that have the important clinical significance.